The effects of expressive writing before or after punch biopsy on wound healing - Robinson, Hayley; Jarrett, Paul; Vedhara, Kavita; Broadbent, Elizabeth (Elsevier, 2017)
Objective: Recent studies have shown that written emotional disclosure (expressive writing) performed in the two weeks prior to wounding improves healing of punch biopsy wounds. In many clinical settings, it would be more practical for patients to perform this intervention after wounding. The aim of this study was to investigate whether expressive writing could speed the healing of punch biopsy wounds if writing was performed after wounds were made.